Bilateral Vocal Cord Paralysis and Cervicolumbar Radiculopathy as the Presenting Paraneoplastic Manifestations of Small Cell Lung Cancer: A Case Report and Literature Review - Jeffrey C. Yeung; C. Elizabeth Pringle; Harmanjatinder S. Sekhon; Shaun J. Kilty; Kristian Macdonald (Case Reports in Otolaryngology)
Introduction. Bilateral vocal cord paralysis (BVCP) is a potential medical emergency. The Otolaryngologist plays a crucial role in the diagnosis and management of BVCP and must consider a broad differential diagnosis. We present a rare case of BVCP secondary to anti-Hu paraneoplastic syndrome. Case Presentation. A 58-year-old female presented to an Otolaryngology clinic with a history of progressive hoarseness and dysphagia. Flexible nasolaryngoscopy demonstrated BVCP. Cross-sectional imaging of the brain and vagus nerves was negative. An antiparaneoplastic antibody panel was positive for anti-Hu antibodies. This led to an endobronchial biopsy of a paratracheal lymph node, which confirmed the diagnosis of small cell lung cancer. Conclusion. Paraneoplastic neuropathy is a rare cause of BVCP and should be considered when more common pathologies are ruled out. This is the second reported case of BVCP as a presenting symptom of paraneoplastic syndrome secondary to small cell lung cancer.